2007
DOI: 10.1089/ast.2006.0076
|View full text |Cite
|
Sign up to set email alerts
|

TD-1HNMR Measurements Show Enantioselective Dissociation of Ribose and Glucose in the Presence of H217O

Abstract: We used Time Domain (1)H Nuclear Magnetic Resonance (NMR) to characterize changes in proton exchange between water and sugar enantiomers at different concentrations of H(2)(17)O (approximately 15-450 mM) and found that dissociation of the (-)-enantiomers of glucose and ribose occurs at significantly higher rates at higher concentrations of H(2)(17)O. The mechanism behind this enantioselective effect is unclear. The hypothesis we propose is that the large magnetic field (B(o) approximately 0.6T) applied during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Enantio-differences in proton exchange behavior were reported earlier in ribose and glucose and were shown to be controlled by the concentration of H 17 (Scorei et al, 2007). We found that such enantio-differences are also present in amino acids (Asn and Ala), where they are (apart from H 17 2 O) also controlled by pH (Cimpoiaş u et al, submitted).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Enantio-differences in proton exchange behavior were reported earlier in ribose and glucose and were shown to be controlled by the concentration of H 17 (Scorei et al, 2007). We found that such enantio-differences are also present in amino acids (Asn and Ala), where they are (apart from H 17 2 O) also controlled by pH (Cimpoiaş u et al, submitted).…”
Section: Resultssupporting
confidence: 75%
“…Time domain 1 H nuclear magnetic resonance (TD-1 HNMR) relaxation parameters were obtained at 298 AE 0.2 K on a 25 MHz spectrometer (Aremi78 TD-LRP, audio filter bandwidth of 1 MHz, B o ¼ 0.589 T with quadrature phase sensitive detector) as reported earlier (Scorei et al, 2007). This approach allows for measurement of a set of key proton exchange parameters, such as R 2 (0); K exchange ; DpK, and M 2 , with 1-2% accuracy (Yeung and Lent, 1987;Steinbrecher et al, 2000;Scorei and Cimpoiaş u, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpected differences between D and L enantiomers of amino acids, peptides and sugars have recently been investigated. [2][3][4][5][6][7] The differential rates of D-and L-tyrosine crystallization was also reported. 8 Nickel and iron are the most abundant transition metals in the earth's crust.…”
Section: Introductionmentioning
confidence: 94%
“…Nemoto et al (2005) investigated the behavior of D and L-alanine in simulated hydrothermal conditions, and determined that L-alanine was more resistant to racemization, so that it consistently produced an enantiomeric excess. Scorei et al (2007) investigated aqueous solutions of Dand L-ribose and glucose, using nuclear magnetic resonance methods to monitor proton exchange between the enantiomers in solution and H 2 17 O that was added as a probe for this purpose. Proton exchange was significantly faster for the (−) enantiomers of both ribose and glucose.…”
mentioning
confidence: 99%